Probe Beam Deflection Study of Au Nanoparticles Supported Into TiO2 Mesoporous Films - Coneo Rodriguez, Rusbel (2024)
Mesoporous thin films modified with nanoparticles of metal (Au) have been used for the fabrication of an ultra-microelectrode array (UMEA). For the first time, UMEAs were studied using probe beam deflection (PBD) and cyclic voltammetry. The study was carried out using the [Fe(CN)6]3- /[Fe(CN)6]4- couple as a redox probe. The electrochemical response is that of an array of nanoelectrodes. The effects of scan rate on the current and PBD signal profiles are discussed in the context of mass transport within the pores and at the solution-electrode interface.The study suggests that the combination of PBD and CV allows a better understanding of the mass transport phenomena in this type of UMEAs of complex architecture.